Linking entrepreneurial leadership and digital literacy competence to firm performance through business innovation - Nandang Nandang; Disman Disman; Janah Sojanah; Hady Siti Hadijah; Heny Hendrayati; Frederic Marimon; Marhadi Marhadi (Universitas Ahmad Dahlan, 2026)
This study examines the relationships between entrepreneurial leadership, digital literacy competence, and business performance, with business innovation as a mediating mechanism. Previous research has frequently examined leadership or digital capabilities separately. 157 owners or managers of micro, small, and medium enterprises in West Java, Indonesia were selected through non-probability purposive sampling. A seven-point Likert scale was used to gather the data. Structural equation modelling–partial least squares was used for analysis. The findings demonstrate that business performance and innovation are positively affected by entrepreneurial leadership. Digital literacy competence has a beneficial impact on company innovation but has no impact on business performance. Business innovation positively affects business performance and significantly mediates the effects of entrepreneurial leadership and digital literacy competence on business performance. These findings highlight innovation as a key pathway through which leadership and digital capabilities improve performance, underscoring the importance of innovation-oriented leadership development and the strategic deployment of digital capabilities to strengthen the competitiveness of micro, small, and medium enterprises. Theoretically, this study contributes to the development of dynamic capabilities theory by demonstrating how entrepreneurial leadership and digital literacy competence enhance firm performance through innovation as a reconfiguration mechanism. In practice, the findings provide policymakers and micro, small, and medium enterprises development programs with insights to focus on strengthening entrepreneurial leadership and innovation-oriented digital capabilities to improve the competitiveness and sustainability of engineering-sector micro, small, and medium enterprises.